DETERMINAN ANGKA PENGANGGURAN DI JAWA TIMUR TAHUN 2007-2017 - Nafie, Agray Vallendzo Bethmarth; Subagiarta, I Wayan; Prianto, Fajar Wahyu (EP FEB UNS, 2020)
This study aims to analyze the factors that influence the unemployment in East Java in 2007-2017. The method used in this study is OLS (Ordinary Least Square). The data used are PDRB, Inflation, Minimum Wages, Population, and Unemployment in 2007-2017 for 7 dis-tricts/cities in East Java Province, data optained from BPS East Java Province. The result showed that 1) PDRB had a negative and significant effect on unemployment in East Java, 2) Inflation had no effect on unemployment in East Java, 3) Minimum Wages had no effect on unemployment in East Java, 4) Population had a positive effect and significant on unemploy-ment in East Java.Keywords: PDRB, Inflation, Minimum Wages, Population, Unemployment